Holizm pedagogiczny i praktyki edukacyjne - Aleksander A. Połonnikow (Problemy Wczesnej Edukacji)
The subject of analysis in the article is the phenomenon of pedagogical holism, which is considered as a necessary condition for the organization and implementation of the pedagogical position. At the same time, orientation at pedagogical training towards one or another hypostatic integrity is considered as a condition limiting the creativity of students in the analysis and creation of qualitatively different forms of pedagogical thinking and activity. The creative position of future teachers is interpreted as one of the mechanisms ensuring overcoming the uniformity of the current education. Hypostasized forms of pedagogical holism are opposed by the discursive holism, which is associated with the refusal of pedagogical training from extra-situational support in the organization of pedagogical knowledge, the establishment of presentism ideology and the pedagogical relativism in educational practices. The operational unit of these practices is an utterance created in the acts of educational interaction. At the same time, the pedagogical utterance loses its dominant position associated with the status of the owner of the integrity of development and becomes one of the judgments in the multifaceted educational polylogue, existing as the integrity that arises in the actual educational interactions it produces.